Detection Methods for Image and Speech Steganalysis in Enhancing Network and Communication Security - Nelson, Sebastian (Journal of Computer Science and Software Applications, 2023)
With the continuous advancement of the Internet and information technology, reliance on multimedia forms such as images and voice for information acquisition and transmission has significantly increased among governments, enterprises, and individuals. Steganography technology, which embeds ciphertext within ordinary information transmission without detection, poses a risk as public channels may become conduits for illicit information exchange. Consequently, research on steganalysis of public channels is crucial to reinforce communication security and prevent covert communications.Given the widespread use of JPEG image data and voice data in network transmissions, steganalysis technology targeting these formats is vital for enhancing network and communication security. To address the potential security risks posed by steganography, this paper proposes a detection method for image and voice information. As steganalysis technology progresses, the features extracted by algorithms have become increasingly complex and higher in dimensionality, resulting in greater computational complexity and higher demands for processing power.